Performing Policy Through Music: Affective Government Communication of the MBG Jingle on TikTok - Muhammad Gantira; Atwar Bajari; Edwin Rizal (FAKULTAS DAKWAH UIN SALATIGA, 2026)
The Free Nutritious Meals Program (MBG) has sparked intense public debate in Indonesia, particularly concerning food safety and public trust. While discussion on text-based platforms are largely dominated by critical and deliberative discourse, less attention has been given to how public responses emerge when the same policy is presented through emotive, music-based content on entertainment oriented platforms. This study aims to investigate how MBG is received when communicated through jingle within TikTok space. Using sentiment analysis as a tool to examine the pattern of audience response. The findings reveal a heterogeneous sentiment expression. Drawing on Arousal Theory and platform affordance perspectives, this study addresses platform affordance shape how the community interact within the space itself. TikTok facilitates policy communication as performative and emotional engagement, where visible positivity reflects platform shaped affective participation rather than policy approval.